Dog team hauling cart with cask of water on the beach at Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Hauling water with dogs Nome Alaska" Original image in Hegg Album 11, page 5. Original photograph by Eric A. Hegg 1218; copied by Webster and Stevens 193.A